Kontribusi Efikasi Diri dan Regulasi Diri Terhadap Pemaafan Diri Remaja yang Sedang Mengalami Masa Hukuman - Muhammad Syukri Siradjuddin; Zulaeni Esita (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The stigma of society in adolescents who experience the process of punishment makes the situation of teenagers worse off. This feeling of sinking occurs because teenagers have not been able to apply self-forgiveness to themselves, thus making themselves feel guilty, and ashamed of themselves. This feeling of shame and guilt occurs because of poor self-efficacy and lack of self-regulation in the teenager. So that self-efficacy and self-regulation are considered very important in bringing up self-forgiveness. This study aims to see how big the contribution of self-efficacy and self-regulation variables to self-forgiveness of adolescents who are undergoing punishment (n=36). Collecting data using a scale of self-regulation, self-efficacy and self-forgiveness then analyzed using regression techniques. The results of the study found that self-efficacy and self-regulation can significantly contribute to adolescent self-forgiveness, this is indicated by the value of f=5.285, probability p=0.01 (p<0.05), and an effective contribution of 24.3%.